Polyethersulfone/polyacrylonitrile blended ultrafiltration membranes: preparation, morphology and filtration properties - Pasaoglu, Mehmet Emin; Guclu, Serkan; Koyuncu, Ismail (Water science and technology, 2016)
Polyethersulfone (PES)/polyacrylonitrile (PAN) membranes have been paid attention among membrane research subjects. However, very few studies are included in the literature. In our study, asymmetric ultrafiltration (UF) membranes were prepared from blends of PES/PAN with phase inversion method using water as coagulation bath. Polyvinylpyrrolidone (PVP) with Mw of 10,000 Da was used as pore former agent. N,N-dimethylformamide was used as solvent. The effects of different percentage of PVP and PES/PAN composition on morphology and water filtration properties were investigated. Membrane performances were examined using pure water and lake water filtration studies. Performances of pure water were less with the addition of PAN into the PES polymer casting solutions. However, long-term water filtration tests showed that PES/PAN blend membranes anti-fouling properties were much higher than the neat PES membranes. The contact angles of PES/PAN membranes were lower than neat PES membranes because of PAN addition in PES polymer casting solutions. Furthermore, it was found that PES/PAN blend UF membranes' dynamic mechanical analysis properties in terms of Young's modules were less than neat PES membrane because of decreasing amount of PES polymer.